Melioidosis in Critical Care: A Review - Sridharan, Sowmya (Indian J Crit Care Med, 2021)
KEY POINTS: (1) Diabetes, hazardous alcohol use, and/or significant heart disease are more likely to develop a critical illness with melioidosis. (2) Pneumonia is the most common presentation. Those with pneumonia or bacteremia are most likely to require intensive care unit admissions. (3) Culture is the mainstay for the diagnosis. However, it is noted that Burkholderia pseudomallei is often wrongly identified as Pseudomonas or other Burkholderia species by commonly available commercial techniques. (4) Therapy consists of an intensive phase with intravenous antibiotics to prevent mortality followed by an eradication phase with oral antibiotics to prevent relapse. (5) Meropenem is the drug of choice for those with septic shock or neurological involvement. For patients with nonpulmonary organ focal sites of infection (neurologic, prostatic, bone, joint, cutaneous, and soft tissue melioidosis), the addition of trimethoprim-sulfamethoxazole (TMP-SMX) to ceftazidime/carbapenem during intensive therapy is recommended. TMP-SMX is the drug of choice for oral antibiotic therapy during the eradication phase. (6) Adequate source control is essential for successful treatment and to prevent relapse. (7) The use of granulocyte-colony stimulating factor (G-CSF) those with septic shock is controversial. HOW TO CITE THIS ARTICLE: Sridharan S, B Princess I, Ramakrishnan N. Melioidosis in Critical Care: A Review. Indian J Crit Care Med 2021; 25(Suppl 2):S161–S165.